Pengaruh Game Edukasi Adventure Berbantuan Online Hots Test Terhadap Keterampilan Berpikir Kritis Siswa - I Gede Eka Saputra (Jurnal Didaktika Pendidikan Dasar, 2021)
Critical thinking is an essential skill that students must have to face the challenges of the 21st century. The low critical thinking skills’ problem is caused by student's internal factors and the learning process doesn't prioritize the development of thinking skills. This study aims to determine the effect of learning media adventure educational games assisted by online tests with the content of higher order thinking skill (HOTS) questions on critical thinking skills. The method in this study is a pre-experiment with One Group Pretest-Posttest Design. The research subjects were class VIIIE at SMPN 1 Tegallalang in the 2019/2020 academic year, with 36 total students. Data collection critical thinking skills using essay tests. The data research analyzed using paired samples test, with the requirement that data normal distributed and homogeneous. The results of the normality and homogeneity test, obtained at a significant level of more than 0,05. So that the data for critical thinking skills normally distributed and homogeneous. The increase in critical thinking skills from the N-Gain analysis of 0,643 in the medium category. Based on the results of the paired samples test, the value of Sig. was obtained (2-tailed) of 0,000 < 0,05, which can be concluded that the use of the adventure educational game assisted the HOTS online test has a significant effect towards students’ critical thinking skills